Immunobiotics and functional foods for the correction and prevention of immune system disorders - Starovoitova, Svitlana (My University, 2017)
There are many reasons a disturbance of intestinal microflora, diet high in polyunsaturated fats, antibiotics, stress, local and systemic inflammatory diseases and others. In many cases, several factors acting simultaneously. The consequences of intestinal microflora disturbance are complex and can cause both local (bowel disease) and systemic (metabolic disease) pathological conditions (Crohn's disease, diabetes, obesity, atopic dermatitis, allergies, etc.). Biological effects of probiotic microorganisms are strain-specific. Depending on the type, species, strain probiotic bacteria can have immunostimulatory, immunodeviatory (bipolar) and immunoregulatory / suppressive effect.
Keywords: immunobiotics; functional food; immune system; disorders; probiotics microorganisms; імунобіотики; функціональні продукти; імунна система; розлади; кафедра біотехнології і мікробіології; иммунобиотики; функциональные продукты; иммунная система; расстройства; кафедра біотехнології і мікробіології